Reidemeister torsion and integrable Hamiltonian systems - Alexander Fel'shtyn; Hector Sánchez-Morgado (International Journal of Mathematics and Mathematical Sciences)
In this paper, we compute the Reidemeister torsion of an isoenergetic surface for the integrable Hamiltonian system on the 4-dimensional symplectic manifold. We use the spectral sequence defined by the filtration and following Floer-Witten ideas we bring into play the orbits connecting the critical submanifolds.